Charge transport investigations of one-dimensional binary and ternary systems of zinc, tin and iron oxides - Girish Karthik K R (2014)
Nanowires of semiconducting metal-oxides have generated a lot of interest due to their unique properties and applications. This work focuses on the analysis of charge transport mechanisms in 1-D ternary metal-oxide nanowires of Zinc (Zn2SnO4 and ZnFe2O4) and its binary constituents(ZnO, SnO2, Fe2O3) using maskless fabrication technique of Focused Ion beam (FIB)/Focused electron Beam (FEB). This investigation encompasses a detailed study of the electrical characteristics of individual nanowire systems and lays foundations in un- derstanding the further architectures in the form of nanojunctions and nanonets. The inves- tigation also includes a comparison of electrical properties between the Ternary and their binary counter parts. The individual metal-oxide nanowires show stable transport characteristics in vacuum, probably due to the depletion of the surface oxygen vacancies. Since the nanowires studied in this work are thick enough to avoid depletion-limited current through the struc- tures, measurements of the space charge limited current (SCLC) allows deriving the majority carrier mobilities from their current-voltage (I-V) characteristic curves. A comparison of the mobilities is performed in the case of Zn2SnO4 nanowires, to portray the validity of SCLC measurements in the chosen systems over FET measurements. Impedance measure- ments are performed on individual Fe2O3 nanorods and nanojunctions to evaluate the im- pact of grain boundaries at the nanojunctions. The same is extrapolated to study the capaci- tance contributions from different regions of the other chosen nanowire systems. The role of defects in forming a ZnO nanowire resistive memory is also evaluated with respect to the vacuum partial pressure. Apart from the device characteristics, fabrication based approaches have also been evaluated with respect device performance. Taking the knowledge from individual nanowire devices, aligned SnO2 nanonets device is investigated with respect to their surface adsorption-desorption in an FET configuration. As their utilization is fast in- creasing, the investigation of the fundamentals of charge transport in nanowires has a deep impact on modern day novel devices like Dye Sensitized Solar Cells (DSSCs), Lithium-ion batteries, Chemical and Biological sensors and Nanoelectronics.